Getting to the Root of Plant‐Mediated Methane Emissions and Oxidation in a Thermokarst Bog. Issue 11 (20th November 2020) - Turner, Jesse C.; Moorberg, Colby J.; Wong, Andrea; Shea, Kathleen; Waldrop, Mark P.; Turetsky, Merritt R.; Neumann, Rebecca B.
Abstract: Vascular plants are important in the wetland methane cycle, but their effect on production, oxidation, and transport has high uncertainty, limiting our ability to predict emissions. In a permafrost‐thaw bog in Interior Alaska, we used plant manipulation treatments, field‐deployed planar optical oxygen sensors, direct measurements of methane oxidation, and microbial DNA analyses to disentangle mechanisms by which vascular vegetation affect methane emissions. Vegetation operated on top of baseline methane emissions, which varied with proximity to the thawing permafrost margin. Emissions from vegetated plots increased over the season, resulting in cumulative seasonal methane emissions that were 4.1–5.2 g m −2 season −1 greater than unvegetated plots. Mass balance calculations signify these greater emissions were due to increased methane production (3.0–3.5 g m −2 season −1 ) and decreased methane oxidation (1.1–1.6 g m −2 season −1 ). Minimal oxidation occurred along the plant‐transport pathway, and oxidation was suppressed outside the plant pathway. Our data indicate suppression of methane oxidation was stimulated by root exudates fueling competition among microbes for electron acceptors. This contention is supported by the fact that methane oxidation and relative abundance of methanotrophs decreased over the season in the presence of vegetation, but methane oxidation remained steady in unvegetated treatments; oxygen was not detected around plant roots but was detected around silicone tubes mimicking aerenchyma; and oxygen injection experiments suggested that oxygen consumption was faster in the presence of vascular vegetation. Root exudates are known to fuel methane production, and our work provides evidence they also decrease methane oxidation. Plain Language Summary: Methane is a greenhouse gas with a greater ability to warm the earth than carbon dioxide. Wetlands are the largest natural source of methane to the atmosphere. To understand future climate change, scientists need to predict the amount of methane released from wetlands. Many factors affect the amount of methane generated by soil microbes (called methane production) and how much methane is released into the atmosphere (called methane emission). Methane traveling through soils can also get converted to carbon dioxide through methane oxidation. Wetland plants influence production, transport, and oxidation of methane, but studies disagree on their overall effect on emissions. In this study, we used multiple methods to identify how plants affect the methane cycle. Plants appeared to increase methane production and, to our surprise, decrease methane oxidation. We created a theory for why plants increased methane emissions, advancing understanding of plant‐soil interactions that contribute to wetland methane emissions. Key Points: In the presence of vascular vegetation, methane production increased and methane oxidation decreased, leading to greater methane emissions Minimal methane oxidation occurred along the plant‐transport pathway, and methane oxidation was suppressed outside the plant pathway Data imply plants decreased oxidation by causing competition between methanotrophs and other heterotrophs for electron acceptors